SECURITY OF INTERNATIONAL TRANSPORT CORRIDORS HOW TO PROVIDE UKRAINE’S NATIONAL SECURITY - Ferdman , G. (Theory and Practice of Public Administration, 2020)
The need to study the problem of MTC security in the conditions of economic instability is conditioned by the need to integrate Ukraine’s transport networks and transport into both the EU transport system and the international transport system. Given the benefits of international transit service, any country does its best to ensure that the ITC passes through its territory. At the same time, transport corridors are important not only for profit, but also a factor that significantly affects the national security of the state. The overriding task of reforming Ukraine’s security system is to build MTC’s transport security, because, both from the perspective of foreign partners and taking into account domestic national interests, the security of the MTC is a prerequisite for their functioning in Ukraine. Deepening cross-border cooperation with neighboring countries is a priority of any country. Cooperation in the sphere of safe functioning of the ITC will surely promote the establishment of close, equal, mutually beneficial relations of Ukraine in the international arena and will enhance the level of Ukraine’s foreign and national security. Among the national security spheres, the MTC has a particular influence on the military and security spheres of Ukraine’s state border. The development of the ITC system in Ukraine will help to maintain the level of operational readiness of the national transport system to use it to ensure the military security of the state. Effective public administration in the area of ​​safe functioning of the MTC will enhance mutual understanding between central and regional authorities, strengthen their authority, and facilitate the granting of greater powers to regional authorities. Ensuring the security of the ITC for Ukraine is of great importance and relevant manifestations also in international, foreign and state policy, national interests and defense capabilities of the state, but above all in the national security of Ukraine. The proposals on the main directions of safe functioning of MTC in Ukraine are given. The conclusions summarize the benefits of Ukraine from the safe development of the MTC, determine the importance of ensuring their security for the state and emphasize that the most manifestation of the safety of the MTC is in the national security of Ukraine.